Ethnicity, socioeconomic status, and overweight in Asian American adolescents - Cook, Won Kim; Tseng, Winston; Bautista, Roxanna; John, Iyanrick (Preventive medicine reports, 2016)
Asian American children and adolescents are an under-investigated subpopulation in obesity research. This study aimed to identify specific profiles of Asian subgroups at high risk of adolescent overweight with special attention to Asian ethnicity, socioeconomic status (SES), and their interaction. Multiple logistic regression models were fitted using a sample of 1533 Asian American adolescents ages 12–17 from the 2007–2012 California Health Interview Survey (CHIS). In addition to Asian ethnicity and socioeconomic status (assessed by family income and parental education level), age, gender, nativity, and two lifestyle variables, fast food consumption and physical activity, were also controlled for in these models. Key predictors of overweight in Asian American adolescents included certain Asian ethnicities (Southeast Asian, Filipino, and mixed ethnicities), low family income (<300% of the Federal Poverty Level), and being male. Multiplicative interaction terms between low family income and two ethnicities, Southeast Asian and Vietnamese that had the lowest SES among Asian ethnic groups, were significantly associated with greatly elevated odds of being overweight (ORs=12.90 and 6.67, respectively). These findings suggest that high risk of overweight in Asian American adolescents associated with low family incomes may be further elevated for those in low-income ethnic groups. Future research might investigate ethnic-group SES as a meaningful indicator of community-level socioeconomic disparities that influence the health of Asian Americans. •Southeast Asian and Filipino ethnicities were associated with adolescent overweight.•Low family income was positively associated with Asian adolescent overweight.•Ethnicity and low family income interacted to increase risk of adolescent overweight.